Obesity and Meniscal Transplant Failure: A Retrospective Cohort Study - Jiménez-Garrido, Carlos; Gómez-Cáceres, Abel; Espejo-Reina, María Josefa; Espejo-Reina, Alejandro; Tamimi, Iskandar; Serrano-Fernández, José Miguel; Dalla Rosa-Nogales, Jaime; Espejo-Baena, Alejandro (The Journal of Knee Surgery, 2019)
The purpose of this study was to analyze the effect of obesity and other clinical factors on the outcome of meniscal allograft transplantation (MAT) with transosseous fixation. A retrospective cohort study was performed on patients who underwent a MAT between 2002 and 2017. All the participants had a minimum follow-up period of 24 months. The variables assessed were age at the time of the transplant, side, sex, transplanted meniscus (lateral/medial), body mass index (BMI), smoking status, and previous surgeries. Lysholm, Tegner, and International Knee Documentation Committee (IKDC) test outcomes, and patient satisfaction were recorded. Image assessment was performed using plain standing X-rays and a follow-up magnetic resonance imaging scan. Thirty-five patients fulfilled the inclusion criteria. The mean follow-up time was of 75.7 standard deviation (SD) 43.4 months. Patients with a BMI ≥ 30 underwent medial meniscal transplants (88.9 vs. 42.3%, p = 0.022, respectively) more frequently. Obese patients had a significantly lower IKDC (48.6 SD 19.9 vs. 61.7 SD 13.1, p = 0.038, power: 57.5%) and Lysholm (60.3 SD 19.2 vs. 79.4 SD 14.3, p = 0.004, power: 88.7%) scores compared with nonobese patients. The satisfaction and Tegner scores were also lower in obese patients (55.6 vs. 80.7%, p = 0.136, and 2.8 SD 1.0 vs. 4.0 SD 1.9, p = 0.104, respectively); however, these differences were not statistically significant. Obese patients had higher rates of meniscal transplant failure compared with nonobese patients (adjusted hazard ratio: 11.8 [95% confidence interval: 1.5–91.4]). No differences were observed between obese and nonobese patients regarding age, sex, side, smoking status, and follow-up time. In this study, a BMI ≥ 30 kg/m2 resulted in higher MAT failure rates. Nonobese patients had better knee functional results compared with obese individuals.
Keywords: meniscal transplant; obesity; meniscus; knee